Sustainability by extraction of bioactive compounds from onion seeds - Mestour, Selma; Meniai, Abdeslam-Hassen; Melloul, Sarra; Louaer, Mehdi (Comptes Rendus. Chimie)
Onion is not just an edible food compound but its seeds can also be an important source of valuable oil with various sensitive applications mainly in pharmaceutical, cosmetic and food fields. This has encouraged the use of a sustainable extraction technique like the supercritical CO2 extraction of oil from local onion seeds, as a clean and green alternative to organic solvent processes. To achieve this, the effects of four key operating parameters like pressure, temperature, particle size and CO2 mass flowrate were investigated in ranges of [150, 250 bars], [35, 65 °C], [0.25, 0.85 mm] and [50, 100 g/min], respectively, using a Box-Behnken experimental design, for a constant extraction time of 3 h. This led to optimal operating conditions of 250 bar, 57 °C, 0.25 mm and 50 g CO2/min for the best oil extraction yield value of 24.36%. Furthermore, gas chromatography-mass spectrometry (GC-MS) was used to identify qualitatively and quantitatively the chemical composition of the onion seed oils. About ten components were identified in the extracts, but with four major ones, namely 9,12-octadecadienoic acid, methyl ester, 9,12-octadecadienoic acid (Z,Z)-, methyl ester, 9-octadecadienoic acid (Z)-, methyl ester and hexadecanoic acid, methyl ester, present with significant percentages, depending on the operating parameters values. These fatty acids are well known for their benefits for human health. Finally this research showed ability of the supercritical CO2 extraction to induce a sustainability character while being performing in producing bioactive substances, excluding the use of organic solvent and even replacing classical and traditional techniques like hydrodistillation.